Menekan Nilai SAIDI SAIFI Pada Penyulang Monkey Forest Dengan Pemasangan D-Star (Doble Isolator Tarik) Dan Perisai Binatang - I Gst. Ketut Abasana; Adiaksa, I Made Anom; I Gde Nyoman Sangka; Ida Bagus Gde Widiantara (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
PT PLN (Persero) ULP Gianyar manages 29 feeders, one of which is the Monkey Forest feeder, distributing electricity to the Monkey Forest area, distributing electricity over an area of ​​7,168,10,232 m2 and a total cable length of 3.65 km supplied by the Payangan substation distributing electricity to 41 distribution substations in the Monkey Forest area with a total of 3,062 customers. Disturbances to the Monkey Forest feeder are dominated by animals because they are located in a tourist location which is a monkey habitat. The D-STAR innovation tool protects against interference caused by animals especially monkeys, in the construction of the stretcher pole at the meeting point/connection of the insulated aerial cable (SKUTM) with the SUTM conductor. Animal shields or what are usually called Cover Bushings are to protect distribution network components from interference caused by animals such as geckos that can easily reach electrical components. The effect of installing the D-STAR innovation tool (double tensile isolator) and animal shield on the SAIDI and SAIFI values ​​in the Monkey Forest feeder is very good, in 2023 the SAIDI value is 1.38 hours/customer/year and the SAIFI value is 1.31 times/customer/year where the value exceeds the target of PLN ULP Gianyar in 2024 after the installation of D-STAR and animal shield the SAIDI value is 0.01 hours/customer/year and the SAIFI value is 0.03 times/customer/year, the value has met the target of PLN ULP Gianyar and SPLN NO 68-2: 1986.